2015
DOI: 10.1038/ijo.2015.32
|View full text |Cite
|
Sign up to set email alerts
|

A multinational examination of weight bias: predictors of anti-fat attitudes across four countries

Abstract: These findings offer new insights and important implications regarding sociocultural factors that may fuel weight bias across different cultural contexts, and for targets of stigma-reduction efforts in different countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
181
5
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(215 citation statements)
references
References 33 publications
20
181
5
9
Order By: Relevance
“…While this may be the Western world's view of obesity, it is worth considering the extent, nature and antecedents of weight bias, as well as similarities and differences in anti-fat attitudes across countries and cultures, as one can assume that there would be a variety of predictors with regard to perceptions of fatness and thinness. Gatineau and Dent (2011) state that perceptions of weight and body image vary within cultures, families and generations, with Puhl, Latner, O'Brien, Luedicke, Danielsdottir and Forhan (2015) adding that it is possible, even if levels of bias were similar across countries, that different predictors may underpin bias in diverse cultures. Stunkard, LaFleur and Wadden (1998) agree stating that cultural upbringing is suggested to be a crucial factor in the development and maintenance of weight bias.…”
Section: The Impact Of Race Culture and Ethnicitymentioning
confidence: 99%
See 1 more Smart Citation
“…While this may be the Western world's view of obesity, it is worth considering the extent, nature and antecedents of weight bias, as well as similarities and differences in anti-fat attitudes across countries and cultures, as one can assume that there would be a variety of predictors with regard to perceptions of fatness and thinness. Gatineau and Dent (2011) state that perceptions of weight and body image vary within cultures, families and generations, with Puhl, Latner, O'Brien, Luedicke, Danielsdottir and Forhan (2015) adding that it is possible, even if levels of bias were similar across countries, that different predictors may underpin bias in diverse cultures. Stunkard, LaFleur and Wadden (1998) agree stating that cultural upbringing is suggested to be a crucial factor in the development and maintenance of weight bias.…”
Section: The Impact Of Race Culture and Ethnicitymentioning
confidence: 99%
“…The latter point refers to the inevitability of producing a desired outcome with effort and ability where, challenging work and determination are seen to lead to success, with failure being due to lack of effort . Puhl et al (2015) examined the extent of weight bias across Canada, the USA, Iceland and Australia and in each nation, attributions of behavioural causes of obesity predicted stronger explicit weight bias, as did beliefs that obesity is attributable to lack of willpower and personal responsibility. There is risk however in relying on selfreported explicit attitude measures, as used in this study, as they do not necessarily translate into behaviour.…”
Section: The Impact Of Race Culture and Ethnicitymentioning
confidence: 99%
“…Discourses (repeated understandings, knowledges, practices) (Foucault & Gordon, 1980;Foucault, 1972;Foucault, 1982) shape not only how a person experiences obesity and their self-identity (see, Wadden & Didie, 2003), but they also shape how others might understand the issue. Since obesity is primarily represented as a matter rooted in personal choice and autonomy, this renders those persons experiencing obesity as persistently stigmatized, misunderstood and held personally responsible for their body weight (Aston, Price, Kirk, & Penney, 2012;Puhl & Kyle, 2014;Puhl et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Weight bias, or discrimination targeted toward those at higher weight statuses, is prevalent both within and outside of the United States (Puhl et al, 2015), resulting in children with obesity being at greater risk for poor social adjustment related to negative interactions with peers, such as name-calling, appearance-related teasing, and bullying (Janssen, Craig, Boyce, & Pickett, 2004;Neumark-Sztainer, Story, & Faibisch, 1998;Pierce & Wardle, 1997;Storch et al, 2006;Thompson et al, 2007). There are also financial implications: adults who are obese spend on average $5,560 per year on healthcare, while individuals who are morbidly obese spend on average $7,010 dollars per year, compared to $4,030 for non-obese individuals (Congressional Budget Office, 2010).…”
Section: Table Of Contentsmentioning
confidence: 99%
“…In particular, longitudinal studies that controlled for sex, age, race, SES, and baseline weight status, found family meal frequency during middle school and high school predicted overweight and obesity status 10 years later Hammons & Fiese, 2011). In terms of peer relations, overweight or obese teens are likely to experience weight-related bullying, name-calling, teasing, and physical aggression by peers (Janssen, Craig, Boyce, & Pickett, 2004;Neumark-Sztainer, Story, & Faibisch, 1998;Puhl et al, 2015). These types of interactions can cause feelings of isolation, as well as anxiety, depression, and lower physical activity (Storch et al, 2007), which could ultimately lead to obesity.…”
Section: Individual Risk Factorsmentioning
confidence: 99%